Redistribution of CO at the location of the CO ice line in evolving gas and dust disks - Stammler, Sebastian Markus; Dullemond, Cornelis (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics